The effectiveness of pre-purchase homeownership counseling: Evidence from a randomized study - Smith, M.; Hochberg, D.; Greene, William (Elsevier BV, 2015)
Homeownership education and counseling have never been rigorously evaluated through a randomized field experiment. This is a five-year study that addresses this shortcoming. The study is structured to respond to the concerns raised about previous efforts. We employ an . experimental design, with study participants randomly assigned to a control or a treatment group. Participants completed a baseline survey and were tracked for four years after receiving initial assistance by means of an annual survey, which also tracks participants' life changes over time. To assist in the analysis, additional information in the form of credit reports and credit scores was obtained annually to track changes in the participants' creditworthiness. Also, certain safeguards were implemented to ensure consistency of the counseling. The study considers the influence of counseling on credit scores, total debt, and delinquencies in payments. We find that those in the treatment group benefit more relative to control participants. Moreover, both treatment participants with one-on-one counseling and control participants who became homeowners tended to pay their mortgages in a timely manner overall.